The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/am3032025
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antimicrobial Thermoplastic Material from Archaeal Poly-γ-l-Glutamate and Its Nanofabrication

Abstract: Here we describe a stoichiometric ion-complex of archaeal poly-γ-L-glutamate (L-PGA) and hexadecylpyridinium cation (HDP(+)), called PGAIC, which shows remarkable chemical resistance and potential as a novel functional thermoplastic. PGAIC films suppressed the proliferation of prokaryotic (Escherichia coli, Bacillus subtilis, Salmonella typhimurium, and Staphylococcus aureus) and eukaryotic (Saccharomyces cerevisiae) microorganisms. Moreover, its antifungal activity was demonstrated against a prevalent species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 21 publications
(41 reference statements)
1
48
0
Order By: Relevance
“…Although PGAIC is an ionic complex, it was unexpectedly stable to chemicals such as salts, acids and alkalis, suggesting the involvement of a driving force in the solidification of PGAIC other than a typical ionic interaction. It is noteworthy that PGAIC exhibits good solubility in alcohols (Ashiuchi et al ., 2013a), whereas PGA itself never dissolves in alcohols. These transformable properties must be taken into account when processing PGA for diverse applications.…”
Section: Chemical Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PGAIC is an ionic complex, it was unexpectedly stable to chemicals such as salts, acids and alkalis, suggesting the involvement of a driving force in the solidification of PGAIC other than a typical ionic interaction. It is noteworthy that PGAIC exhibits good solubility in alcohols (Ashiuchi et al ., 2013a), whereas PGA itself never dissolves in alcohols. These transformable properties must be taken into account when processing PGA for diverse applications.…”
Section: Chemical Transformationmentioning
confidence: 99%
“…Ashiuchi and colleagues (2013a) recently demonstrated that a compound used in toothpaste, called hexadecylpyridinium cation (HDP + ), serves as a potent candidate to suppress the extreme hydrophilicity of PGA. In fact, a water-insoluble complex was readily formed by mixing PGA and HDP + at 60°C for 30 min.…”
Section: Chemical Transformationmentioning
confidence: 99%
“…In the archaeal domain, toxin-antitoxin system genes have been identified in Thermoplasmatales, several methanotrophs, and in the symbiotic archaeon, Nanoarchaeum equitans [64,65]. One study also mentions the use of a stoichiometric ion-complex of archaeal poly-g-Lglutamate and hexadecylpyridinium cation, called PGAIC, which showed antimicrobial activity against several bacterial and eukaryotic microorganisms, and was suggested for use as an antimicrobial coating agent [66].…”
Section: Other Antimicrobial Compoundsmentioning
confidence: 99%
“…Hexadecylpyridinium chloride (HDP) that includes a quaternary ammonium cation (Figure 1) is known as a disinfectant (Johansen et al, 2006). Quaternary ammonium cation binds to the carboxylic acid group of γ-PGA via an ionic bond, and water-insoluble and antimicrobial complexes are thus formed (Ashiuchi et al, 2013;Ashiuchi et al, 2015). Therefore, we hypothesized that it is possible to purify γ-PGA from the culture broth using the water-insoluble complex.…”
Section: Introductionmentioning
confidence: 99%